Integrated control and monitoring of a smart charging station with a proposed data exchange protocol. Issue 3 (10th December 2021) - Monadi, Mehdi; Farzin, Hossein; Salehizadeh, Mohammad Reza; Rouzbehi, Kumars
Abstract: Expansion of electric vehicles' (EVs') charging stations is an unavoidable requirement in sustainable cities. Provision of safe protection and control infrastructure is one of the most important requirements for a reliable charging station. In this direction, a centralized protection, control and monitoring unit (PCMU) for smart charging stations is proposed here. PCMU communicates with chargers of the station, protective devices (e.g. relays and circuit breakers), local generating units and all other devices installed at the charging station to determine the station status and to detect/locate faults that may occur in the supply grid of the station. The PCMU includes a self‐healing technique which is one of the specialties of smart systems that assists network reliability to increase. One of the major contributions of this research is to propose a protocol for data exchange between the PCMU and the other components similar to the logic used in standard of IEC 61850. Also, potential impacts of implementation of the proposed unit on the most‐widely used reliability indices are discussed. The proposed protection strategy is examined via two case studies.